Childhood trauma and relationship with the parents: associations with lipids, glucose, and prolactin levels during antipsychotic treatment in patients with first-episode psychosis - Marianne Laffely; Claire Grosu; Nermine Laaboub; Philippe Golay; Philippe Golay; Luis Alameda; Luis Alameda; Luis Alameda; Luis Alameda; Philippe Conus; Philippe Conus; Chin B. Eap; et al. (Frontiers in Psychiatry)
BackgroundBesides antipsychotics and other clinical factors, childhood trauma (CT) may also alter metabolic and endocrine profiles. The aim was to determine whether CT influence metabolic profiles and prolactin levels in patients with first-episode psychosis treated with antipsychotics for up to one year. The quality of the relationship with the parents was also investigated.MethodsTwo hundred twenty-six patients with low-density lipoprotein (LDL), high-density lipoprotein (HDL), non-HDL, total cholesterol, triglycerides, fasting plasma glucose, and prolactin levels monitored routinely before and during antipsychotic treatment were included. CT refers to physical, sexual, or emotional abuse occurring before the prodromal phase and up to 16 years old and was assessed during the patients’ 3 years follow-up. The quality of the relationship with parents was assessed at the beginning of the follow-up.ResultsAfter 12 months, CT was associated with an increase in total and non-HDL cholesterol levels (+17%, 95%CI:[0.4; 34]; +11%, 95%CI:[0.4; 21], respectively). Lack of a good relationship with the father was associated at 2 and 12 months with above-median levels of LDL (OR=5.5, 95%CI:[1.3, 28]; OR=3.7, 95%CI:[1.3; 12], respectively) and non-HDL (OR=4.7, 95%CI:[1.3; 19]; OR=2.8, 95%CI:[1.0; 8.0], respectively). Lack of a good relationship with the mother was associated with higher baseline prolactin levels in women (124 ng/ml, 95%CI:[91; 157]) and increased total cholesterol levels after 2 and 12 months (21%, 95%CI:[5.9; 36]; 12%, 95%CI:[1.1; 24]), respectively).ConclusionChildhood trauma or a lack of a good relationship with one parent is associated with worse metabolic and prolactin profiles in first-episode psychosis patients during the first year of antipsychotic treatment.